Physical activity levels and sedentary behaviour according to sex, age, BMI, academic year, and country among medical students in Latin America - Diego Herreros-Irarrázabal; María Fernanda González-López; Rocío Nuche-Salgado; Josivaldo de Souza-Lima; Sandra Mahecha-Matsudo (BMC, 2024)
Abstract Physical inactivity represents a global challenge in public health, being the second most significant factor contributing to mortality. In Latin America, the prevalence of physical inactivity and sedentary behaviour is notable, affecting medical students as well, who play a crucial role as behavioural role models for the population. This study addresses the prevalence of physical activity and sedentary behaviour among medical students in Latin America during the year 2023. A total of 864 participants from 12 institutions across eight countries were surveyed using the Global Physical Activity Questionnaire. Significant variations in physical activity and sedentary behaviour were observed according to sex, age, body mass index, academic year, and country. Notably, Costa Rica exhibited the highest levels of moderate physical activity in leisure time (90 min/day). Strength training was more common among men (60 min/day) and in Argentina (60 min/day). Sedentary behaviour was higher in women (420 min/day) and during the first academic year (485 min/day). Uruguay stood out with high levels of sedentary behaviour (600 min/day). Correlations indicated positive moderate associations between academic year and moderate leisure-time PA (r:0,128, p:0,007). In conclusion, there are associations between the level of physical activity and sedentary behaviour with the variables studied in this research, with the main findings being that the female sex has more time spent in sedentary behaviour (minutes/day) and less time spent in strength training (minutes/day). Additionally, there are higher levels of sedentary behaviour in the early years of medical study compared to the later years of the program.